Enhanced expression of Organic Cation Transporters in bronchial epithelial cell layers following insults associated with asthma – impact on salbutamol transport - Mukherjee, Manali; Cingolani, Emanuela; Pritchard, D.I.; Bosquillon, Cynthia (Elsevier, 2017)
Increasing evidence suggests Organic Cation Transporters (OCT) might facilitate the absorption of inhaled bronchodilators, including salbutamol, across the lung epithelium. This is essentially scarred and inflamed in asthma. Accordingly, the impact of epithelial insults relevant to asthma on OCT expression and salbutamol transport was evaluated in air-liquid interfaced layers of the human broncho-epithelial cell line Calu-3. These were physically injured and allowed to recover for 48 h or exposed to the pro-inflammatory stimulant lipopolysaccharide (LPS) for 48 h and the aeroallergen house dust mite (HDM) for 8 h twice over 48 h. Increases in transporter expression were measured following each treatment, with the protein levels of the OCTN2 subtype consistently raised by at least 50%. Interestingly, OCT upregulation upon LPS and HDM challenges were dependent on an inflammatory event occurring in the cell layers. Salbutamol permeability was higher in LPS exposed layers than in their untreated counterparts and in both cases, was sensitive to the OCT inhibitor tetraethylammonium. This study is the first to show epithelial injury, inflammation and allergen abuse upregulate OCT in bronchial epithelial cells, which might have an impact on the absorption of their substrates in diseased lungs.